(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The research addresses the necessity of developing a methodology for creating prospective strategic plans to enhance the effectiveness of coaching activities. Innovative methods for developing strategic managerial skills of coaches, improving athletes’ performance, and effectively organizing sports organizations’ activities are proposed. Practical recommendations are provided for modernizing the management system of coaching activities based on decisions and directives aimed at developing sports in Uzbekistan.